PROFIL KINETIKA PERUBAHAN KADAR GLUKOSA PADA NASI DALAM PEMANAS - Islamiyah, Ukuwah; Gonggo, Siang Tandi; Pursitasari, Indarini Dwi (Jurnal Akademika Kimia, 2013)
Rice cooker is used to keep rice warm and soft. During the warming process there is a change in glucose level in rice. The kinetic profile of glucose level change of rice in rice cooker is important to be done to determine an ideal time needed so that rice is suitable for consumption. The objective of this study is to determine constant reaction rate, reaction order, reaction speed, and half time of glucose level changes of rice in rice cooker. Method of this study is phenol-sulfuric acid, where modest sugar react with phenol in concentrated sulfuric acid produce a stabil orange colour, by using uv-vis that is bsorbed in 490 nm wavelength. The research’s result shows that there is a decreasing on glucose level in rice of mbramo type that is 32.2 ppm to 5.8 ppm for 40 hours kept in rice cooker. The changesof glucose level of rice in rice cooker following equation of one order reaction, with value of constant reaction speed achieved is 3.8 x 10-2/hour, half time 18.2 hours and reaction speed 0.5 ppm/hour.